Glycodinameric Hydrogels Based on Chitosan and a Vanillin Isomer - Manuela Maria Iftime; Florentina Georgescu; Alina Nicolescu; Luminita Marin; Florin Oancea (Proceedings)
Hydrogels are a promising class of materials addressing a plethora of applications in biomedicine, environmental protection and agriculture [...]